Pengaruh retail mix terhadap purchase decision pada pelanggan lotte mart di cabang fatmawati Jakarta Selatan - VITA BRILIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The main purpose of the research is to examine the influence of retail mix (Customer Service, Store Design and Display, Communucation Mix, Location, Merchandise Assortment, Pricing) on purchase decision of customer Lotte Mart in Fatmawat ibranch, South Jakarta. The sampling in the study was accidental sampling and uses 60 responded. The respondent of the research is people who attended and buy grocery in Lotte Mart, Fatmawati branch Jakarta. This research uses partial least square analysis.The result has shown that Customer Service, Store Design and Display, Communication Mix, Location, Pricing influence on purchase decision for customers Lotte Mart branch Fatmawati in South Jakarta.But in other hand, Merchandise Assortment doesn't influence on purchase decision for customer Lotte Mart branch Fatmawati, South Jakarta.